Influence of the National Values Curriculum on Pupils’ Cognitive and Emotional Development in Basic Schools in Zamfara State, Nigeria - Sule Muhammad; Sani Ahmadu Gurjiya (CV Media Inti Teknologi, 2026)
Background: Recognizing the critical role of holistic National Value Education in shaping intellectual, moral, and emotional capacities, the research examined how structured value-based instruction affects reasoning, problem-solving, empathy, cooperation, and moral sensitivity among pupils. Objective: The study investigated the influence of the National Values Curriculum (NVC) on pupils’ cognitive and emotional development in basic schools in Zamfara State, Nigeria. Methods: A correlational research design was employed, with a sample of 384 pupils drawn through a multi-stage sampling technique from both urban and rural schools. Data were collected using a validated and reliable self-developed questionnaire, the National Values Curriculum Influence Questionnaire (NVCIQ), and analyzed using descriptive statistics, Pearson correlation, and independent samples t-tests. Results: The findings revealed a strong positive relationship between the NVC and pupils’ cognitive development (r = 0.675, p < 0.001), as well as emotional development (r = 0.618, p < 0.001), indicating that increased exposure to the curriculum significantly enhances both intellectual and affective competencies. Gender differences in cognitive development were not statistically significant, while school location had a significant impact on emotional development, with urban pupils demonstrating higher affective skills than rural pupils. Conclusion: The study concludes that the NVC effectively promotes holistic development, fostering responsible, morally grounded, and socially competent pupils. It recommends continuous teacher training, provision of adequate instructional resources, and the incorporation of interactive and reflective activities to maximize the curriculum’s cognitive and emotional benefits.